US foreign policy after the Cold War : global hegemon or reluctant sheriff? - Cameron, Fraser, 1947- (Routledge, 2005)
Since the success of the best-selling first edition, the world has remained fascinated with US foreign policy, not least because of the far-reaching consequences of the US led invasion of Iraq. This fully updated textbook follows the events of the past two and a half years including the 2004 presidential campaign, whilst still providing a comprehensive introduction to all aspects of American foreign policy. Chapter headings include:from colony to superpowerthe post-Cold War decadethe role of Congressthe media and public opinionthe.